Molecular characterization of western corn rootworm pyrethroid resistance. Issue 2 (3rd October 2020) - Souza, Dariane; Siegfried, Blair D; Meinke, Lance J; Miller, Nicholas J
Abstract: BACKGROUND: Western corn rootworm (WCR) pyrethroid resistance has been confirmed in the western US Corn Belt. Toxicological and biochemical studies indicated that multiple mechanisms of resistance might be involved in the resistance trait, such as enhanced metabolism and/or kdr target‐site mutation(s) in the voltage‐gated sodium channels. To characterize the mechanisms of WCR pyrethroid resistance at the molecular level, pairwise comparisons were made between RNA‐Seq data collected from pyrethroid‐resistant and ‐susceptible WCR populations. Gene expression levels and sodium channel sequences were evaluated. RESULTS: Seven transcripts exhibited significantly different expression ( q ≤ 0.05) when comparing field‐collected pyrethroid‐resistant (R‐Field) and ‐susceptible (S‐Field) WCR populations. Three of the differentially expressed transcripts were P450s overexpressed in R‐Field (9.2–26.2‐fold). A higher number (99) of differentially expressed transcripts was found when comparing laboratory‐derived pyrethroid‐resistant (R‐Lab) and ‐susceptible (S‐Lab) WCR populations. Eight of the significant transcripts were P450s overexpressed in R‐Lab (2.7–39.8‐fold). This study did not detect kdr mutations in pyrethroid‐resistant WCR populations. Other differentially expressed transcripts that may play a role in WCR pyrethroid resistance are discussed. CONCLUSION: This study revealed that P450‐mediated metabolism is likely to be a major mechanism of WCR pyrethroid resistance, which could affect the efficacy of other insecticides sharing similar metabolic pathways. Additionally, results suggested that although laboratory selection of a pyrethroid‐resistant WCR population may help to characterize resistance mechanisms, a field‐selected population provided rare and perhaps major variants corresponding to the resistance trait. Abstract : Western corn rootworm (WCR) pyrethroid resistance has been confirmed in the western US Corn Belt. This research evaluates differential gene expression of pyrethroid‐resistant WCRs and reveals a major resistance mechanism. © 2020 Society of Chemical Industry